2023
DOI: 10.1177/17455057231213737
|View full text |Cite
|
Sign up to set email alerts
|

Carrying an unintended pregnancy to term and long-term maternal psychological distress: Findings from the Dutch prospective Amsterdam Born Children and their Development study

Wieke Y Beumer,
Tessa J Roseboom,
Marjette H Koot
et al.

Abstract: Background: Given the estimated high rate of unintended pregnancies, it is important to investigate long-term effects on psychological distress in women carrying an unintended pregnancy to term. However, research into associations between unintended pregnancies carried to term and psychological distress postpartum is mixed, and especially, evidence on long-term associations is scarce. Objective: To examine whether carrying an unintended pregnancy to term is associated with maternal psychological distress later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 70 publications
(113 reference statements)
2
5
0
Order By: Relevance
“…The first peaking, but then disappearing effect of unintended pregnancy on children is in line with trends found in other studies examining over-time effects of unintended pregnancy (34). Further, this is in line with previous results showing disappearing risks of unintended pregnancy on maternal mental health over time (11).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The first peaking, but then disappearing effect of unintended pregnancy on children is in line with trends found in other studies examining over-time effects of unintended pregnancy (34). Further, this is in line with previous results showing disappearing risks of unintended pregnancy on maternal mental health over time (11).…”
Section: Discussionsupporting
confidence: 93%
“…People who carried an unintended pregnancy to term reported poorer bonding and mental health, which in turn was associated to psychosocial problems of the child . This is in line with previous studies, which found that people carrying an unintended pregnancy to term reported poorer maternal bonding (14) and more mental health problems in the first years postpartum (11). Thus, current results stress the importance of maternal mental health for children, which appeared to be a stronger factor contributing to children’s psychosocial problems than pregnancy unintendedness.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Unintended pregnancy is associated with decreased maternal-fetal attachment [ 10 ] and can lead to inadequate prenatal care and nutrition, resulting in adverse outcomes for both the mother and the child [ 11 ]. The type of unintended pregnancy, whether it is mistimed or unwanted, has a significant relationship with maternal-fetal attachment, with mistimed pregnancies showing higher levels of attachment compared to unwanted pregnancies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%